2018
DOI: 10.17265/2161-6256/2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Magnetizing Irrigation Water Impacts on the Enhancement of Yield and Water Productivity for Some Crops

Abstract: Magnetic water treatment is considered as one of many techniques used worldwide that affects plant growth and development. This study examines whether there are beneficial effects of magnetic treatment of irrigation water on yield and water productivity as well as water saving. Three experiments were performed involving three crops (eggplant, faba beans and tomato) with different salinity tolerance thresholds EC w 0.7, 1.1 and 1.7 dS/m, respectively. Two types of irrigation water were applied magnetically trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…This led to water savings of 11%, 14.2%, and 13.5% for the three crops, respectively, ultimately increasing the net profit. Using magnetic treatment technique, the ratios of the net return per water unit to that of using untreated water were 1.97, 2.45, and 3.0 for eggplant, tomato, and faba beans, respectively [57].…”
Section: Mw Effects On Seeds Germination and Plant Growthmentioning
confidence: 96%
See 1 more Smart Citation
“…This led to water savings of 11%, 14.2%, and 13.5% for the three crops, respectively, ultimately increasing the net profit. Using magnetic treatment technique, the ratios of the net return per water unit to that of using untreated water were 1.97, 2.45, and 3.0 for eggplant, tomato, and faba beans, respectively [57].…”
Section: Mw Effects On Seeds Germination and Plant Growthmentioning
confidence: 96%
“…The exposure of water to a magnetic field results in alterations of its basic properties such as ionic strength, pH, and surface tension force, providing greater movement capacity by intensifying the internal vibration of water molecules, which improve the polarizing effect, resulting in an increase of water uptake into the cell [56]. Kareem [57] evaluated the effect of magnetized water irrigation on soil pH. Their results showed that pH decreased to near neutral levels.…”
Section: Mw Effects On Seeds Germination and Plant Growthmentioning
confidence: 99%
“…El riego con ATM también puede aumentar el rendimiento y la calidad de cultivos como maíz, remolacha azucarera, Berenjenas, habas y tomate (Aladjadjiyan, 2002;Hozayn et al, 2013;Nessrien, 2018). Ensayos en condiciones de campo en cultivos de arroz (Oryza sativa) irrigados con agua normal y ATM (110 mT), revelaron que la irrigación con ATM generó un aumento en el crecimiento, la concentración de pigmentos fotosintéticos, los carbohidratos totales y las proteínas totales (Babaloo et al, 2018).…”
Section: Protección Contra El Estrés Abióticounclassified
“…Irrigation water with magnetic field to become magnetized water could accelerate plant growth, enhance crop yield, save irrigation water and reduce the effect of deficit irrigation on crop growth and yield (Kareem, 2018;Abd-Ellateef and Mutwali, 2020;Abou El-Yazied, 2011). Surendran et al (2016) reported that magnetization of irrigation water improved cow pean's growth rate and yield using magnetic flux densities of 1800 -2000 G when the water was allowed to flow through the magnetic field for 10 minutes and a flow rate of 2 liters/s.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Surendran et al (2016) reported that magnetization of irrigation water improved cow pean's growth rate and yield using magnetic flux densities of 1800 -2000 G when the water was allowed to flow through the magnetic field for 10 minutes and a flow rate of 2 liters/s. Kareem (2018) reported that irrigating tomato plant with magnetized water increased the water use efficiency (water productivity) by 78% and the yield of tomatoes by 52.68%. Sadeghipour and Aghaei (2013) also pointed out that magnetized water increased water use efficiency of cowpea by 22%.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%